2006
DOI: 10.1042/bst0340356
|View full text |Cite
|
Sign up to set email alerts
|

Sterol trafficking between the endoplasmic reticulum and plasma membrane in yeast

Abstract: We recently showed that transport of ergosterol from the ER (endoplasmic reticulum) to the sterol-enriched PM (plasma membrane) in yeast occurs by a non-vesicular (Sec18p-independent) mechanism that results in the equilibration of sterol pools in the two organelles [Baumann, Sullivan, Ohvo-Rekilä, Simonot, Pottekat, Klaassen, Beh and Menon (2005) Biochemistry 44, 5816-5826]. To explore how this occurs, we tested the role of proteins that might act as sterol transporters. We chose to study oxysterol-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 26 publications
(22 reference statements)
3
83
0
Order By: Relevance
“…Some studies suggest that the yeast Osh proteins mediate intracellular sterol transport, as a yeast strain deficient of all the seven Osh proteins shows a significant reduction in PM -ER sterol transfer (Raychaudhuri et al 2006;Sullivan et al 2006). Other studies, however, suggest that Osh proteins regulate sterol transport indirectly by affecting actin dynamics (Fairn and McMaster 2008), regulating phosphoinositides levels, and/or by regulating the assembly/stability of MCSs.…”
Section: Lipid Transport From the Ermentioning
confidence: 99%
“…Some studies suggest that the yeast Osh proteins mediate intracellular sterol transport, as a yeast strain deficient of all the seven Osh proteins shows a significant reduction in PM -ER sterol transfer (Raychaudhuri et al 2006;Sullivan et al 2006). Other studies, however, suggest that Osh proteins regulate sterol transport indirectly by affecting actin dynamics (Fairn and McMaster 2008), regulating phosphoinositides levels, and/or by regulating the assembly/stability of MCSs.…”
Section: Lipid Transport From the Ermentioning
confidence: 99%
“…4. The ergosterol transport rate needed for cell growth is calculated as follows (55 that bind the surface of Osh4p (Fig. 2) were also transferred, albeit at a lower rate (28).…”
Section: Revisiting the Case For Osh Proteins As Stpsmentioning
confidence: 99%
“…Examination of a requirement of these Osh proteins for sterol equilibration from the ER to the plasma membrane, however, revealed only a moderate, five-fold delay in mutants lacking Osh function, indicating that Osh proteins may not be sterol transporters by themselves, but that they affect sterol transport indirectly, for example by affecting the ability of the plasma membrane to sequester sterols [9]. The transport of sterols back from the plasma membrane to the ER, however, requires Osh function and is greatly reduced in mutants that fail to synthesize certain phosphoinositide phosphates (PIPs), indicating that PIPs modulate sterol transfer by the Osh proteins, which is consistent with the presence of a PIP-binding pleckstrin homology domain in a subset of the Osh proteins [14].…”
Section: Sterol Uptake and Transport Pathways In Yeastmentioning
confidence: 99%
“…As in mammalian cells, ergosterol is synthesized in the ER, from where it is transported by a poorly characterized mechanism to the plasma membrane, the major ergosterol containing membrane in yeast [8]. Recent characterization of the nature of this forward transport pathway has revealed that the newly synthesized ergosterol equilibrates with a half-time of 10e15 min with the plasma membrane-localized sterol pool, which corresponds to the transport of approximately 10 5 ergosterol molecules into and out of the plasma membrane per second [9]. This equilibration is independent of the secretory pathway, but delayed in mutant cells that have reduced levels of sphingolipids [10].…”
Section: Sterol Uptake and Transport Pathways In Yeastmentioning
confidence: 99%